Automated auditory brainstem response in preterm newborns with histological chorioamnionitis. (6th November 2014) - Smit, Adriana L.; Been, Jasper V.; Zimmermann, Luc J. I.; Kornelisse, Rene F.; Andriessen, Peter; Vanterpool, Sizzle F.; Bischoff, Martijn P. H.; Stokroos, Robert J.; de Krijger, Ronald R.; Kremer, Bernd; Kramer, Boris W.
Abstract: Objective : We investigated whether histological chorioamnionitis is associated with an adverse neonatal hearing outcome. Methods : Two cohorts of very preterm newborns ( n = 548, gestational age ≤ 32.0 weeks) were linked to placental histology and automated auditory brainstem response (AABR) outcome. Results : In multivariable analyses, an abnormal AABR was not predicted by the presence of histological chorioamnionitis, either with or without fetal involvement (OR 1.4, 95% CI 0.5 – 3.8, p = 0.54 and OR 1.1, 95% CI 0.4–3.0, p = 0.79, respectively). Significant predictors of abnormal AABR included, e.g. birth weight (per kg increase: OR 0.2, 95% CI 0.0–0.6, p = 0.006), umbilical cord artery pH (per 0.1 increase: OR 0.7, 95% CI 0.5–0.9, p = 0.005) and mechanical ventilation (OR 3.7, 95% CI 1.2–11.6, p = 0.03). Conclusions : Histological chorioamnionitis was not associated with an adverse neonatal hearing outcome in two cohorts of very preterm newborns. Indicators of a complicated neonatal clinical course were the most important predictors of an abnormal hearing screening.